Lanthanoid “Bottlebrush” Clusters: Remarkably Elongated Metal-Oxo Core Structures with Controllable Lengths - D'Alessio, Daniel; Sobolev, A.; Skelton, B.; Fuller, Rebecca; Woodward, R.; Lengkeek, N.; Fraser, B.; Massi, Massimiliano; Ogden, Mark (American Chemical Society, 2014)
Large metal-oxo clusters consistently assume spherical or regular polyhedral morphologies rather than high-aspect-ratio structures. Access to elongated core structures has now been achieved by the reaction of lanthanoid salts with a tetrazole-functionalized calixarene in the presence of a simple carboxylate coligand.The resulting Ln19 and Ln12 clusters are constructed from apex-fused Ln5O6 trigonal bipyramids and are formed consistently under a range of reaction conditions and reagent ratios. Altering the carboxylate coligandstructure reliably controls the cluster length, giving access to a new class of rod-like clusters of variable length.